ANALISIS PRAKTIK JUAL BELI KUE BASAH DENGAN SISTEM KONSINYASI DI BLOK PUNDUAN DESA MEKARJAYA GANTAR INDRAMAYU MENURUT TINJAUAN HUKUM EKONOMI ISLAM - Al Fithri, Arsy; Syafi’i, Moch.; Maulana, Rizal (Cahaya Ilmu Bangsa, 2024)
This research examines the practice of buying and selling moist cakes through consignment systems and the Islamic legal perspective on buying and selling moist cakes through consignment systems in Desa Mekarjaya, Gantar, Indramayu. The main issues addressed in this research are the practice of buying and selling moist cakes through consignment systems in Blok Punduan, Desa Mekarjaya, Gantar, Indramayu, and the Islamic economic law perspective on the practice of buying and selling moist cakes through consignment systems in Blok Punduan, Desa Mekarjaya, Gantar, Indramayu. The objectives of this research are to understand the practice of buying and selling moist cakes through consignment systems and to understand the Islamic legal perspective on the practice of buying and selling moist cakes through consignment systems in Blok Punduan, Desa Mekarjaya, Gantar, Indramayu. This research method employs field research with a qualitative approach. Data collection procedures include interviews, observations, and documentation. The results of the research indicate that the practice of buying and selling moist cakes through consignment systems involves the consignor handing over the moist cakes produced to the consignee to be sold to buyers. Agreements between consignors and consignees are made orally. The distribution is determined based on the consignee's status, wherein if the consignee is a local resident, the wage distribution is 70% for the consignor and 30% for the consignee, whereas if the consignee is a newcomer, the wage distribution is 80% for the consignor and 20% for the consignee. The practice of buying and selling moist cakes through consignment systems in Blok Punduan, Desa Mekarjaya is in accordance with Islamic economic law, as viewed from the aspects of Islamic economic law principles and the akad ju'alah aspect. Keywords: Moist Cakes, Consignment, Islamic Economic Law